(untitled) (The Journal of Geography Education in Africa, 2023)
We live in a socio-ecologically fragile and rapidly changing world that can be turned upside down in an instant as we witnessed with the crisis of the COVID-19 pandemic. Today, more than ever before, teachers need to be life-long learners who have the necessary geography subject knowledge, pedagogical knowledge and resources for responsive teaching and learning in their classrooms. Professional Learning Communities (PLCs) play an important enabling role in this regard. This article presents the findings of the second phase of an ongoing study aimed at understanding how the South African Geography Teachers’ online Google Group, an emergent Professional Learning Community, may support and enhance geography education and teacher professional development. More specifically, it opens up and looks inside the ‘black box’ of the Google Group, the workings of which are not yet fully understood. It considers the supportive role played by the Google Group during and after the COVID-19 pandemic (that is, March 2020 to December 2021 and January to November 2022). Data generated by the posts made during and after the pandemic, were analysed and categorised. Emergent patterns and trends in and between the two periods were identified and discussed. A purposive sample from each category was selected for further in-depth analysis. We draw on Shulman and Shulman’s (2004) theory of teacher knowledge as an analytical lens for interpreting the findings. The findings are discussed in relation to national imperatives (for example, teacher professional development, social justice, inequality and learner underperformance) and global education discourses for transformative education. Our main contention in this article is that the Google Group PLC offers support for teachers. However, there are gaps that need to be addressed if it is to play a stronger supportive and transformative role. We conclude with some suggestions on how this may be achieved in practice which may be useful to members of the geography education community particularly teachers. Key words: teacher knowledge, teacher professional development, professional learning community, COVID-19 pandemic